CERITA BERGAMBAR SEBAGAI KONKRETISASI PEMBELAJARAN SASTRA ANAK DI SEKOLAH DASAR - Putra, Jalu Norva Illa; Widyaningsih, Nina (Universitas PGRI Yogyakarta, 2020)
This community service activity aims to train teachers to make learning media in the form of pictorial stories with children's literary content. This article is a case study of community service at the Nakula Gugus Teacher Working Group in Wonogiri, Central Java. Children's literature in this context is defined as a medium that is used as an intermediary to convey a form of character education for children. Apart from this, children's literature is considered an appropriate medium because it is able to attract students' interest through visual and narrative forms. Children's literature is also able to have more appeal if from the beginning it comes from ideas that are owned by the children themselves. This will stimulate a sense of ownership and logic to the things that the story structure wants to instill. The method used is lectures and discussions, then in the form of workshops on picture story books. The result of this community service is a picture book with a theme that is close to children related to the use of gadgets, which are then given the title Playing with Friends.